Análise química e topográfica da neoformação óssea por distração osteogênica em mandíbula de ovelhas com uso de laserterapia : estudo piloto - Blaya, Diego Segatto (2012)
Objectives: To conduct a preliminary analysis of the therapeutic effects of laser therapy (830nm) with regard to surface topography (scanning electron microscopy - SEM) and chemical composition (energy dispersive spectrometry - EDS) of the newly formed bone during distraction osteogenesis (DO) combined with low-level laser therapy (LLLT) in an experimental sheep model. Methods: Five female Corriedale sheep weighing 40 to 45kg (experimental units A, B, C, D, and E) were treated with LLLT at different stages of OD, as follows: sheep A, B, and C received the first irradiation session immediately after closure of the surgical wound and new sessions then every 48 hours (at a total of eight sessions); sheep D received the first irradiation session on the last day of device activation, followed by seven additional applications every 48 hours (at a total of eight sessions); sheep E (control) was not irradiated. Bone samples were analyzed via SEM at 80x, 300x, and 1000x magnification, and EDS spectra, at 300x magnification. Results: According to the Student t test for paired samples, the medullary bone of sheep mandibles treated with DO presented statistically higher mean values of carbon and calcium when compared with untreated mandibles (controls). The internal and external cortical layers did not show statistically significant differences in relation to reference values (p > 0.05). Bone surface topography was very similar in all specimens. Conclusion: Infrared laser therapy as used in our study (GaAlAs, 830nm, 50mW power, cutaneous irradiation at three sites, and energy density of 5J/cm2 per session at a total of 120J/cm2), has benefits when applied at the beginning of the bone consolidation period, suggesting an increased hardness and resistance of the newly formed bone tissue